Ruta aviturística en la Parroquia Alluriquin, canton Santo Domingo de la provincia de Santo Domingo de los Tsáchilas, periodo marzo 2020 – septiembre 2020. - Días Quijo, Franklin Damián (2020)
The present work allowed the study and design of an Aviturist Route in the parish of Alluriquín, Santo Domingo canton, in the province of Santo Domingo de los Tsáchilas during the period May-September 2020; which allowed the analysis of data and primary and secondary information of the sector. It was determined that the parish has two climatic floors: the tropical mega thermal humid and the equatorial mesothermal semi humid. Five zones were also determined for the collection of information, being the ones that have the climatic, geographical and topographical conditions to house several species that are found in the mentioned climatic floors. At the same time, field trips were carried out to determine and register the species that were recognized by means of bird watching methods such as point counting and intensive search, as well as the use of TICS (Merlin, Ebird) and GPS tools, for the compilation and validation of data that served to raise the inventory that had around 228 species, being 42% in relation to the birds of the province and 13% of the birds of Ecuador. Similarly, 18 orders were obtained, of which the one that maintained the highest number of families with a total of 20 and 144 species that represent 63.15% of the total wealth was the Passeriform order and the one with the lowest percentage was attributed to the Strigiform order with 1 family and 1 species that represents 0.44% of the total wealth, This information was validated thanks to the platform of the Red Book of Birds of Ecuador and the Red List of the IUCN (International Union for Conservation of Nature), which allowed the identification of 15 species in a vulnerable state, among them the Crested Guan, Red-Masked Parakeet, Dusky Pigeo, Fasciated Tiger-Heron, Plate-billed Mountain-Toucan, Cinnamon Woodpecker, Russet Antshrike and the endangered Long-wattled Umbrellabird. This information was systematized by means of the methodological orientation of the Manual of Tourist Routes and Itineraries where the components of the route and the itinerary are indicated, obtaining as a result the Aviturist Route of the Alluriquín parish with a route of 23 km in the five zones, with a duration of five days through a geographic space that goes from 699 to 2229 meters above sea level through primary, secondary and intervened forests with a first and second order road, and that has 2 bird guides, 3 hotels for accommodation, a public transport service and 2 private, as well as 3 restaurants for food. These are key factors to develop the activities in the Route.